Bridging the Gap between Academia and Practice: Project-Based Class for Prestressed Concrete Applications - Islam M. Mantawy; Conner Rusch; Sushil Ghimire; Lucas Lantz; Hari Dhamala; Bipesh Shrestha; Anthony Lampert; Mohit Khadka; Anima Bista; Rhytham Soni; Abdulu Saleem Shaik; Eric Lujan; et al. (MDPI AG, 2019)
Educational approaches in structural engineering have focused on classical methods for solving problems with manual calculations through assignments, quizzes, and exams. The use of computational software to apply the learned knowledge has been ignored for decades. This paper describes an educational approach to tackle the lack of applicable practical exercises in the structural engineering class "CE 506-Prestressed Concrete" at a university in the western United States during the spring of 2017. The class was designed to provide students with the theoretical concepts of prestressed concrete and the ability to interpret applicable design codes. In their project, students continued to build this knowledge by designing a prestressed bridge superstructure according to a unique state design manual. Students prepared a literature review of their selected state in the U.S.A. and used commercial software to perform an analysis and design of their bridge. Additionally, students were asked to backcheck their design using theoretical methods through manual calculations. By the end of the class, students presented their projects in a head-to-head presentation format, to contrast the differences between their designs in a competitive style. This paper summarizes the class structure, the outcome of the design project, and recommendations for future applications of computer technology in structural engineering education.